New opportunities in tuberculosis prevention: implications for people living with HIV. Issue 1 (8th January 2020) - González Fernández, Lucia; Casas, Esther C; Singh, Satvinder; Churchyard, Gavin J; Brigden, Grania; Gotuzzo, Eduardo; Vandevelde, Wim; Sahu, Suvanand; Ahmedov, Sevim; Kamarulzaman, Adeeba; Ponce‐de‐León, Alfredo; Grinsztejn, Beatriz; et al.
Abstract: Introduction: Tuberculosis (TB) is a leading cause of mortality among people living with HIV (PLHIV). An invigorated global END TB Strategy seeks to increase efforts in scaling up TB preventive therapy (TPT) as a central intervention for HIV programmes in an effort to contribute to a 90% reduction in TB incidence and 95% reduction in mortality by 2035. TPT in PLHIV should be part of a comprehensive approach to reduce TB transmission, illness and death that also includes TB active case‐finding and prompt, effective and timely initiation of anti‐TB therapy among PLHIV. However, the use and implementation of preventive strategies has remained deplorably inadequate and today TB prevention among PLHIV has become an urgent priority globally. Discussion: We present a summary of the current and novel TPT regimens, including current evidence of use with antiretroviral regimens (ART). We review challenges and opportunities to scale‐up TB prevention within HIV programmes, including the use of differentiated care approaches and demand creation for effective TB/HIV services delivery. TB preventive vaccines and diagnostics, including optimal algorithms, while important topics, are outside of the focus of this commentary. Conclusions: A number of new tools and strategies to make TPT a standard of care in HIV programmes have become available. The new TPT regimens are safe and effective and can be used with current ART, with attention being paid to potential drug‐drug interactions between rifamycins and some classes of antiretrovirals. More research and development is needed to optimize TPT for small children, pregnant women and drug‐resistant TB (DR‐TB). Effective programmatic scale‐up can be supported through context‐adapted demand creation strategies and the inclusion of TPT in client‐centred services, such as differentiated service delivery (DSD) models. Robust collaboration between the HIV and TB programmes represents a unique opportunity to ensure that TB, a preventable and curable condition, is no longer the number one cause of death in PLHIV.